The Effect of Using the Livin' by Mandiri Application on Customer Satisfaction and Loyalty Using the Utaut Model - Anita Rismaharni Syaputri; Khairani Ratnasari Siregar (Return : Study of Management, Economic and Bussines, 2025)
The rapid development of digital technology in Indonesia, including the banking sector, is reflected in internet penetration reaching 79.5% of the total population by 2024. Digital transformation driven by the government has also significantly boosted the growth of the digital economy, with a value of US$82 billion in 2023 and projected to increase to US$109 billion in 2025 (BPS, 2024; Dhanesworo, 2024). The banking sector continues to innovate through digital services, one of which is the Livin' by Mandiri application. The adoption of technology by the younger generation is a factor in the success of this application, where millennials and Gen Z account for 77% of total users. This study aims to evaluate the effect of using the livin' by mandiri application on customer satisfaction and loyalty using the UTAUT model. The method used in this study is a quantitative approach. Data was collected through an online survey involving 203 respondents who are active users of the Livin by Mandiri application. The analysis technique uses Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationship between variables and measure the level of influence of each variable in the research model. The results of this study indicate that the actual usage variable has a positive and significant effect on customer satisfaction, which shows the large contribution of the intensity of application use to the level of user satisfaction. In addition, actual usage also has a positive and significant effect on attitudinal loyalty, which indicates that the experience of using the application can form a loyal attitude of customers towards the Livin' by Mandiri application. Thus, the more frequently and effectively the application is used, the higher the customer satisfaction and loyal attitude formed.